PENGARUH KINERJA KEUANGAN DAN TATA KELOLA TERHADAP NILAI PERUSAHAAN PADA SEKTOR KESEHATAN DI BURSA EFEK INDONESIA TAHUN 2022-2023 - Desi Oktaviana Simanjuntak; Calen Calen; Eko D. M. Siringo Ringo (JOURNAL SAINS STUDENT RESEARCH, 2024)
This study aims to determine the effect of corporate governance aand financial performance on firm value in sub-sector health which listed in the Indonesia stock exchange 2020-2023. Indicator of corporate governance using commite audit. Financial performance with ROA as well firm value with tobin’s q. this type of research use quantitative research. Data collection techniques were carried out by secondary methods. Data analysis was carried out using multiple linear analysis. The result indicated that committee audit, ROA had a effect on firm value. Meanwhile, committe audit has no effect on firm value.